Challenges that novices face in applying core concepts to neuroscience contexts - Cooper, Keiland W.; Tran, Eric H.; McIntosh, Brandon O.; Lam, Tien; Tat, Chau-man T.; Gallegos, Diana M.; Dukes, Angeline J.; Chen, Audrey (Frontiers in Education, 2025)
General Education (GE) courses field students from different majors with varied preconceptions of the life sciences, and neuroscience in particular. To aid instruction, outcomes, and assessment of students, core concepts are an effective tool that utilizes conceptual elements to promote learning and the transfer of knowledge between disciplines. This study examined students' prior understanding of two core concepts shared across biology and neuroscience—structure-function relationship and evolution—within the student population enrolled in GE neuroscience courses. The structure-function relationship core concept focuses on how characteristics of structures enable or constrain their function and vice versa, while the evolution core concept focuses on how similarities and differences in nervous systems between organisms are shaped by their shared ancestry and adaptations to their environments. Responses were analyzed using a deductive coding approach aimed to classify responses based on proficiency of conceptual understanding either within a general biology context or a neuroscience-specific context. Analysis revealed that the majority of non-biologists at the start of an introductory neuroscience course were unable to demonstrate comprehension of the structure-function (83.4%) or evolution core concept (67.0%) in either a general biology or neuroscience-specific context. Further inductive coding identified common themes that emerged from student responses, revealing student preconceptions of the Structure-function relationship and Evolution core concepts based on student major. These findings can aid educators by informing their selection of background information during course design and presentation of the material to positively shape students' understanding of these core concepts in GE classes.